EFFICIENCY OF ANIMAL FOLDING CONTAINER / GOODS CONTAINER (CARGO) SUPPORTING SEA TOLL - Sutini; Mudji Astuti Handadjani; Ismiyati (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Pelayaran Malahayati, 2023)
The islands in Indonesia can only be connected through the seas between the islands. The sea is not a separator, but a unifier of various islands, regions and regions of Indonesia. Only through inter-island inter-coastal relations can the unity of Indonesia be realized. Shipping that connects the islands is the lifeblood of life as well as unifying the nation and state of Indonesia. The Port of Tenau Kupang is a fairly large sea port in the province of East Nusa Tenggara. Throughout the year, ships arrive at the port to transport various kinds of goods. One of the cargoes loaded at the port dock is general cargo. At this time, almost all general cargo is shipped using containers because it is considered safer during transportation and the loading process is faster. Therefore, loading of containers into ships has to be carried out using ship's cranes, but sometimes also assisted by mobile cranes from land. Thus, the time for unloading containers from ships is relatively long. The purpose of the voyage by bringing beef cattle other than to Surabaya is to Banjarmasin. Wooden ships departing from ports of origin such as Bima and Sheets to Banjarmasin, in addition to carrying cattle, also carry other agricultural products such as shallots, soybeans, and salt. Meanwhile, ships departing from the destinations of Bima and Sheets to Surabaya generally carry corn, soybeans, and cattle. The folding container model for transporting animals from Kupang - Surabaya supports the marine highway. . The purpose of this research is the selection of animal folding container models as a supporter of the Kupang – Surabaya sea toll route help expedite logistics delivery and help the welfare of the community, both in food delivery (living things, even ready-to-eat), while making containers as a special model for animal loads has a huge impact on the distribution of food needs. Based on the binomial logit method in the selection of modes here, it will get what percentage of the choice of modes to be selected, then simulated with the degree of preference of users of transportation mode services which are analyzed using the stated preference method. The research method is a mix of descriptive - quantitative methods. The result of this research is a folding container ship transportation model as a supporter of the marine highway.